2017
DOI: 10.1007/978-3-319-50174-1_2
|View full text |Cite
|
Sign up to set email alerts
|

Structural Perspectives on Sigma-1 Receptor Function

Abstract: The sigma-1 receptor is an enigmatic ER-resident transmembrane protein linked to a variety of human diseases. Although the receptor was first cloned 20 years ago, the molecular structure of the protein and the mechanistic basis for its interaction with drug-like small molecules have remained unclear until recently. The determination of the first crystal structure of human sigma-1 offered the first detailed views of the sigma-1 architecture, and revealed an unusual overall fold with a single transmembrane helix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…This topology was consistent with evidence that BiP, an ER luminal chaperone protein, binds to the C-terminal domain of Sig-1R ( Hayashi and Su, 2007 ). However, a crystal structure of Sig-1R challenges these observations because it identified only a single TMD within each subunit of a trimeric complex, and it placed the C-terminal region on the cytosolic side of the ER membrane ( Alon et al., 2017 , Schmidt et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…This topology was consistent with evidence that BiP, an ER luminal chaperone protein, binds to the C-terminal domain of Sig-1R ( Hayashi and Su, 2007 ). However, a crystal structure of Sig-1R challenges these observations because it identified only a single TMD within each subunit of a trimeric complex, and it placed the C-terminal region on the cytosolic side of the ER membrane ( Alon et al., 2017 , Schmidt et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…TMEM97 is located in the ER and has the ability to regulate the sterol transporter Niemann-Pick disease, type C1 Protein (NPC1) (Alon et al., 2017b). In that study, the authors found that its pharmacologic profile is the same as that of Sigma-2 receptor; moreover, TMEM97 ligands bind Sigma-2 receptors (Alon et al., 2017a). A new study has also shown that Sigma-2 receptor/TMEM97 is involved in alcohol withdrawal behaviors, indicating that this receptor can be targeted to treat alcohol use disorder (Scott et al., 2018).…”
Section: The Introduction Of Sigma Receptorsmentioning
confidence: 90%
“…Sigma1R has a unique amino acid sequence and has no homology with known mammalian proteins [43,44]. In 2016 the crystal structure of a protein with one transmembrane domain for each monomer was determined under the general supervision of Andrew C. Kruse [45,46]. Sigma1R oligomerization affects the chaperone functional activity and depends on the interaction with ligands [41,[47][48][49][50].…”
Section: Structure and Functional Activity Of The Chaperone Sigma1rmentioning
confidence: 99%